Natural Magnetic Particles/Chitosan Impregnated with Silver Nanoparticles for Antibacterial Agents - Annisa Afra Martha; Defia Indah Permatasari; Elma Retna Dewi; Nikho Asyoka Wijaya; Eko Sri Kunarti; Bambang Rusdiarso; Nuryono Nuryono (Indonesian Journal of Chemistry, 2022)
In this research, silver nanoparticles (AgNP) impregnated on natural magnetic material/chitosan composite (NMP/Chi) have been conducted with different AgNP concentrations (0.5, 1.0, 1.5 mM). Their antibacterial activity was examined against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). The AgNP samples were characterized with UV-Vis spectrophotometer and TEM. The NMP/Chi/AgNP samples were identified with FTIR and XRD, while NMP/Chi/AgNP1.0 (with the highest antibacterial activity) were analyzed with TEM and SEM-EDX. The antibacterial test with a well-diffusion method showed that NMP/Chi/AgNP was categorized as a strong antibacterial agent. The composite showing the largest inhibition zone diameters was NMP/Chi/AgNP prepared using 1.0 M AgNO3, namely 14.39 and 16.8 mm against E. coli and S. aureus, respectively. Characterization of AgNP1.0 showed a spherical shape with an average particle diameter of 17.9 nm in suspension and 32.4 nm in NMP/Chi. The presence of 1000 mg/kg NMP/Chi/AgNP1.0 composite in water was able to reduce the growth of E. coli and S. aureus bacteria by 60.4% (from 5.3 to 2.1 CFU/mL) and 71.6% (from 6.34 to 1.86 CFU/mL), respectively, within 5 h. The NMP/Chi/AgNP1.0 showed an effective antibacterial agent against both bacteria (E. coli and S. aureus) and could be applied potentially in aquatic environments.